KARAKTERISTIK WISATAWAN YANG MENGINAP DI HOMESTAY DAN PERSEPSI WISATAWAN MENGENAI UBUD SEBAGAI DESTINASI WISATA - Chintia Pinaria; Ida Ayu Kalpikawati; I Gusti Agung Febrianto (Pusat penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2021)
Ubud is one of the world's tourist destinations in Gianyar Regency, Bali. Ubud has a wellpreserved artistic and cultural attraction. The number of tourist visits to Ubud continues to increase every year and is directly proportional to the increase in the number of homestay accommodations. In addition to the growing number of tourists and homestays, another interesting thing to observe about Ubud as a tourist destination is news about traffic jams and damaged infrastructure. This study aims to determine the characteristics of tourists staying at homestays in Ubud and tourists' perceptions of Ubud as a tourist destination. The data collection technique used is through distributing questionnaires. The research approach used in this research is descriptive quantitative. Respondents in this study were tourists who stayed at homestays as many as 319 respondents. Tourists' perceptions of Ubud as a tourist destination are rated not good and quite good. The point that gets a bad rating is that the roads in Ubud can be passed smoothly. This must immediately get special attention from the government and the community to solve the problem so that the image of Ubud as a leading tourist destination in Bali can be maintained properly.